COVERT COMMUNICATION FOR COOPERATIVE NOMA WITH TWO PHASES DETECTION - Peng, Hongxing; Tian, Zhifa; Li, Xingwang; Wang, Weizheng; Nauryzbayev, Galymzhan; Rabie, Khaled; Gadekallu, Thippa Reddy (Alexandria Engineering Journal, 2022)
This paper investigates the covert communication of cooperative non-orthogonal multiple access (NOMA) systems, where the near user serves as a decode-and-forward (DF) relay and the far user receives the covert information from both the source and the near user. To improve the covertness performance, cooperative jamming and power randomness are adopted. Specifically, we derive detection error probability (DEP) of Willie and the minimum detection error probability (MDEP) at the optimal decision threshold for each phase. In addition, the reliability of the proposed system is investigated by deriving closed-form expressions for the outage probability (OP) of the two users. Under the covertness and reliability constraints, an optimization algorithm to maximize the effective covert rate is designed. Simulation results have confirmed the correctness of the theoretical analysis, and the proposed scheme can achieve a better covert communication.
Keywords: Type of access: Open Access; Covert communication; Cooperative communication; Detection error probability; Non-orthogonal multiple access